Development of a Luliconazole Nanoemulsion as a Prospective Ophthalmic Delivery System for the Treatment of Fungal Keratitis: In Vitro and In Vivo Evaluation - Jingjing Yang; Zhen Liang; Ping Lu; Fei Song; Zhen Zhang; Tianyang Zhou; Jingguo Li; Junjie Zhang (MDPI AG, 2022)
Luliconazole (LCZ), a novel imidazole drug, has broad-spectrum and potential antifungal effects, which makes it a possible cure for fungal keratitis; nevertheless, its medical use in ocular infections is hindered by its poor solubility. The purpose of this study was to design and optimize LCZ nanoemulsion (LCZ-NE) formulations using the central composite design-response surface methodology, and to investigate its potential in improving bioavailability following ocular topical administration. The LCZ-NE formulation was composed of Capryol 90, ethoxylated hydrogenated castor oil, Transcutol® P and water. The shape of LCZ-NE was spherical and uniform, with a droplet size of 18.43 ± 0.05 nm and a low polydispersity index (0.070 ± 0.008). The results of an in vitro release of LCZ study demonstrated that the LCZ-NE released more drug than an LCZ suspension (LCZ-Susp). Increases in the inhibition zone indicated that the in vitro antifungal activity of the LCZ-NE was significantly improved. An ocular irritation evaluation in rabbits showed that the LCZ-NE had a good tolerance in rabbit eyes. Ocular pharmacokinetics analysis revealed improved bioavailability in whole eye tissues that were treated with LCZ-NE, compared with those treated with LCZ-Susp. In conclusion, the optimized LCZ-NE formulation exhibited excellent physicochemical properties, good tolerance, enhanced antifungal activity and bioavailability in eyes. This formulation would be safe, and shows promise in effectively treating ocular fungal infections.